2000
DOI: 10.1038/sj.onc.1203693
|View full text |Cite
|
Sign up to set email alerts
|

Smad-dependent stimulation of type I collagen gene expression in human skin fibroblasts by TGF-β involves functional cooperation with p300/CBP transcriptional coactivators

Abstract: Transforming growth factor-b (TGF-b) stimulation of Type I collagen gene (COL1A2) transcription involves the Smad signal transduction pathway, but the mechanisms of Smad-mediated transcriptional activation are not fully understood. We now demonstrate that the ubiquitous transcriptional coactivators p300 and CREB-binding protein (CBP) enhanced basal as well as TGF-b-or Smad3-induced COL1A2 promoter activity, and stimulated the expression of endogenous Type I collagen. The adenoviral E1A oncoprotein abrogated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
199
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(209 citation statements)
references
References 61 publications
8
199
0
1
Order By: Relevance
“…Therefore, one of the possible mechanisms by which abrogation of Smad3 gene expression prevented bleomycin-induced lung fibrosis may be mediated by having a direct negative effect on collagen expression in mouse lungs. However, it is also possible that reduction of collagen expression in bleomycin-treated Smad3 null mutant lungs is mediated by other indirect effects, such as increased expression of the transcriptional coactivator p300/CBP or reduced expression of the TGF-␤ pathway inhibitor Smad7 (9,27). The molecular mechanism of Smad3 action on collagen expression needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the possible mechanisms by which abrogation of Smad3 gene expression prevented bleomycin-induced lung fibrosis may be mediated by having a direct negative effect on collagen expression in mouse lungs. However, it is also possible that reduction of collagen expression in bleomycin-treated Smad3 null mutant lungs is mediated by other indirect effects, such as increased expression of the transcriptional coactivator p300/CBP or reduced expression of the TGF-␤ pathway inhibitor Smad7 (9,27). The molecular mechanism of Smad3 action on collagen expression needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences have shown that Smad3 is involved in the transcriptional activation of TGF-␤-mediated stimulation of collagen expression (5,32,33). Smad3 is necessary for the formation of transcriptional activation complex in the stimulation of type I collagen gene expression by TGF-␤ ligands in human skin fibroblasts (6,9). Smad3 also acts synergistically with transcriptional factor TFE3 to activate TGF-␤-induced transcription of the plasminogen activator inhibitor-1 gene (16).…”
Section: Discussionmentioning
confidence: 99%
“…56 The transcriptional coactivators p300/CBP enhance basal as well as TGF-␤-or Smad3-induced collagen ␣2(I) promoter activity, and stimulate the expression of endogenous type I collagen in human dermal fibroblasts. 57 No comparable element has been identified in the collagen ␣1(I) gene.…”
Section: Discussionmentioning
confidence: 99%
“…The SMAD pathway plays a fundamental role in regulation of collagen synthesis, and SMADs are necessary to mediate TGF␤-dependent stimulation (29)(30)(31)(32)(33). In light of the singular importance of TGF␤ in both initiating and sustaining fibroblast activation, and given the pivotal role of SMADs as major intracellular effectors of TGF␤-induced profibrotic responses, we undertook extensive characterization of SMAD signaling in a large panel of scleroderma fibroblasts.…”
mentioning
confidence: 99%
“…To prevent protein dephosphorylation, a Phosphatase Inhibitor Mix (Sigma, St. Louis, MO) was added. Nuclear extracts were prepared as previously described (31). Protein concentrations in the cytosolic, nuclear, or whole cell fractions were determined by Bradford assay (Bio-Rad, Hercules, CA).…”
mentioning
confidence: 99%